How Does the dGEMRIC Index Change After Surgical Treatment for FAI? A Prospective Controlled Study: Preliminary Results - Schmaranzer, Florian (Clin Orthop Relat Res, 2016)
BACKGROUND: Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) allows an objective, noninvasive, and longitudinal quantification of biochemical cartilage properties. Although dGEMRIC has been used to monitor the course of cartilage degeneration after periacetabular osteotomy (PAO) for correction of hip dysplasia, such longitudinal data are currently lacking for femoroacetabular impingement (FAI). QUESTIONS/PURPOSES: (1) How does the mean acetabular and femoral dGEMRIC index change after surgery for FAI at 1-year followup compared with a similar group of patients with FAI treated without surgery? (2) Does the regional distribution of the acetabular and femoral dGEMRIC index change for the two groups over time? (3) Is there a correlation between the baseline dGEMRIC index and the change of patient-reported outcome measures (PROMs) at 1-year followup? (4) Among those treated surgically, can dGEMRIC indices distinguish between intact and degenerated cartilage? METHODS: We performed a prospective, comparative, nonrandomized, longitudinal study. At the time of enrollment, the patients’ decision whether to undergo surgery or choose nonoperative treatment was not made yet. Thirty-nine patients (40 hips) who underwent either joint-preserving surgery for FAI (20 hips) or nonoperative treatment (20 hips) were included. The two groups did not differ regarding Tönnis osteoarthritis score, preoperative PROMs, or baseline dGEMRIC indices. There were more women (60% versus 30%, p = 0.003) in the nonoperative group and patients were older (36 ± 8 years versus 30 ± 8 years, p = 0.026) and had lower alpha angles (65° ± 10° versus 73° ± 12°, p = 0.022) compared with the operative group. We used a 3.0-T scanner and a three-dimensional dual flip-angle gradient-echo technique for the dGEMRIC technique for the baseline and the 1-year followup measurements. dGEMRIC indices of femoral and acetabular cartilage were measured separately on the initial and followup radial dGEMRIC reformats in direct comparison with morphologic radial images. Regions of interest were placed manually peripherally and centrally within the cartilage based on anatomic landmarks at the clockface positions. The WOMAC, the Hip disability and Osteoarthritis Outcome Score, and the modified Harris hip score were used as PROMs. Among those treated surgically, the intraoperative damage according to the Beck grading was recorded and compared with the baseline dGEMRIC indices. RESULTS: Although both the operative and the nonoperative groups experienced decreased dGEMRIC indices, the declines were more pronounced in the operative group (−96 ± 112 ms versus −16 ± 101 ms on the acetabular side and −96 ± 123 ms versus −21 ± 83 ms on the femoral side in the operative and nonoperative groups, respectively; p < 0.001 for both). Patients undergoing hip arthroscopy and surgical hip dislocation experienced decreased dGEMRIC indices; the decline in femoral dGEMRIC indices was more pronounced in hips after surgical hip dislocation (−120 ± 137 ms versus −61 ± 89 ms, p = 0.002). In the operative group a decline in dGEMRIC indices was observed in 43 of 44 regions over time. In the nonoperative group a decline in dGEMRIC indices was observed in four of 44 regions over time. The strongest correlation among patients treated surgically was found between the change in WOMAC and baseline dGEMRIC indices for the entire joint (R = 0.788, p < 0.001). Among those treated nonoperatively, no correlation between baseline dGEMRIC indices and change in PROMs was found. In the posterosuperior quadrant, the dGEMRIC index was higher for patients with intact cartilage compared with hips with chondral lesions (592 ± 203 ms versus 444 ± 205 ms, p < 0.001). CONCLUSIONS: We found a decline in acetabular, femoral, and regional dGEMRIC indices for the surgically treated group at 1-year followup despite an improvement in all PROMs. We observed a similar but less pronounced decrease in the dGEMRIC index in symptomatic patients without surgical treatment indicating continuous cartilage degeneration. Although treatment of FAI is intended to alter the forces acting across the hip by eliminating impingement, its effects on cartilage biology are not clear. dGEMRIC provides a noninvasive method of assessing these effects. Longer term studies will be needed to determine whether the matrix changes of the bradytrophic cartilage seen here are permanent or clinically important. LEVEL OF EVIDENCE: Level II, therapeutic study.